Analisis SWOT terhadap Pemanfaatan Data Konsumen dalam Mendukung Pengambilan Keputusan Bisnis pada UMKM di Kalimantan Barat - Ria Risti Astanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize consumer data as a basis for business decision-making. This study aims to analyze the role of consumer data utilization in supporting business decision-making among MSMEs in West Kalimantan using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) method. The study employed a descriptive method with qualitative and quantitative approaches. The research was conducted from September to October 2025 involving 50 MSME owners representing several districts and cities in West Kalimantan. The respondents consisted of culinary businesses (40%), fashion and handicraft businesses (30%), and beauty product businesses (30%). Data were collected through observation, interviews, questionnaires, and literature studies. The results revealed that WhatsApp customer data was the most widely utilized source of consumer data (92%), followed by customer purchase data (88%), Instagram and Facebook follower data (84%), Shopee marketplace data (76%), and customer complaint data (68%). SWOT analysis indicated that MSMEs in West Kalimantan were positioned in Quadrant I (Growth Oriented Strategy), suggesting that internal strengths and external opportunities were more dominant than weaknesses and threats. Therefore, the recommended strategy is an aggressive growth strategy through optimizing data-driven digital marketing, developing products based on customer needs, and implementing a more integrated customer data management system.